Krüppel-like factors in endothelial cell biology. Issue 3 (May 2017) - Chang, Eugene; Nayak, Lalitha; Jain, Mukesh K.
Abstract : Purpose of review: Krüppel-like factors (KLFs) are a family of transcription factors that regulate integral functions of endothelial cells including inflammation, proliferation, growth, apoptosis, cell differentiation and plasticity, and migration. This review will focus on the role of KLFs in physiological activity and their loss in vascular pathology. Recent findings: New studies have pointed at the role of microRNAs as repressors of KLFs in atherosclerotic areas providing another level of signaling regulation of KLFs. Summary: KLFs are important regulators of almost all facets of endothelial biology, making them a promising therapeutic target in the treatment of endothelial dysfunction and cardiovascular disease. Further research is needed to fully characterize their functions.